Pengaruh Penggunaan Metode Multisensori Terhadap Kemampuan Mengingat Huruf Hijaiyah Anak Usia Dini - Muhammad Rizal Zaenulloh; Arif Ahmad Fauzi; Alfidoh Khoirunnisa (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2025)
This study aims to examine the effect of the multisensory method on early childhood students’ ability to memorize hijaiyah letters and to compare its effectiveness with conventional teaching methods. The study was limited to children in groups B1 and B2 at RA Al Istiqomah Ciranjang. A quantitative approach with a Quasi-Experimental design and a Nonequivalent Control Group Design was employed. The subjects consisted of 13 children in the experimental group and 19 children in the control group. Data were collected through pre-test and post-test assessments, observations, interviews, and documentation. The multisensory method was applied over five sessions, engaging multiple senses through activities such as letter cards, synthetic sand, songs, games, and writing exercises. The results indicated a significant improvement in the experimental group’s ability to memorize hijaiyah letters, with average scores increasing from 28.71 to 67.94 (Sig. < 0.001), while the control group showed a slight increase from 42.10 to 44.73. ANCOVA analysis confirmed a significant difference between the two groups (Sig. < 0.001) with a large effect size (Partial Eta Squared = 0.684). The study concludes that the multisensory method is effective and suitable for early childhood hijaiyah letter learning.